Rancang Bangun Aplikasi E-Donor untuk Pendataan Donor Darah di PMI Kota Surabaya - Robby Kurniawan Budhi (Jurusan Teknologi Informasi Universitas Semarang, 2017)
Blood Donor activities have become Government Programs that provide many benefits, not only to donor recipients but also to donors. Each year, PMI targets up to 4.5 million bags of blood in accordance with national blood requirements, adjusted to the World Health Organization (WHO) standard of 2% of the population for each day. Therefore, regular blood donor activities are always held. But not everyone can donate blood every time. There are health prerequisites and a minimum grace period for someone to be able to re-donor. Not everyone knows the information about this blood donor activity. In addition, often active donors forget the time of re-donor. E-Donor application to be built is trying to solve the problem. Application development using System Development Life Cycle method. As a first step, the scope of the study is limited to PMI coverage in Surabaya.